2016
DOI: 10.1177/0954410016670421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inlet distortion on the performance of axial transonic contra-rotating compressor

Abstract: The present paper numerically conducted full-annulus investigation on the effects of circumferential total pressure inlet distortion on the performance and flow field of the axial transonic counter-rotating compressor. Results reveal that the inlet distortion both deteriorates the performance of the upstream and downstream rotors resulting in reduction of total pressure ratio, efficiency and stall margin of the transonic contra-rotating compressor. Regarding the development of distortion inside compressor, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…5 that the difference between the curves (three investigated cases) is higher at higher rotational speeds (except for 100% speed line in which SCM has higher computational errors). It is worth to mention that the prior research such as Liu et al (2016), Naseri and Boroomand (2016), mainly focused on a specific rotational speed, and no study has been conducted for different revolution. Effects of inlet distortion on fan efficiency are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 that the difference between the curves (three investigated cases) is higher at higher rotational speeds (except for 100% speed line in which SCM has higher computational errors). It is worth to mention that the prior research such as Liu et al (2016), Naseri and Boroomand (2016), mainly focused on a specific rotational speed, and no study has been conducted for different revolution. Effects of inlet distortion on fan efficiency are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has an important role on the stall inception process. Liu et al (2016) investigated the effect of inlet distortion on the performance of an axial transonic contra-rotating compressor by means of full-annulus simulation. Results revealed that the inlet distortion leads to reduction of the pressure ratio and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that the effect of radial distortion on the stability of the fan was negligible. The effect of circumferential total pressure inlet distortion on the performance of a transonic contra-rotating compressor was numerically investigated by Liu et al 12 The interaction between the leakage flow and the detached shock wave at the leading edge of the rear rotor (and the ensuing blockage) was suggested to be one of the reasons for stall inception. Manas and Pradeep 13 investigated the effect of speed combination on stall inception in a contra-rotating fan.…”
Section: Introductionmentioning
confidence: 99%
“…The steady three-dimensional vortex structure of stator under transition conditions was established, and the mechanism of the stalling process was revealed from the perspective of the vortex structure evolution. Liu et al 22 conducted numerical investigation to reveal that the inlet distortion deteriorates the performance of both the upstream and downstream rotors resulting in reduction of total pressure ratio, efficiency, and stall margin of the transonic contrarotating compressor. To improve the flow in transonic compressor, Hu and Wang 23 proposed a compressor design concept by increasing the axial velocity of the rotor outlet to reduce the degree of reaction for the sake of avoiding the flow separation.…”
Section: Introductionmentioning
confidence: 99%